A randomized pilot study on the effect of niacin on pulmonary arterial pressure. Issue 1 (December 2015) - McNamara, Martin; Sayanlar, Jason; Dooley, Daniel; Srichai, Monvadi; Taylor, Allen
Abstract Background Niacin induces the release of vasodilating prostaglandins, for which receptors are present within the pulmonary arterial circulation. We hypothesized that immediate-release niacin would reduce right ventricular systolic pressure in patients with pulmonary hypertension in a randomized, double-blinded, single-dose provocation study. Methods We recruited inpatient subjects with a Doppler echocardiogram showing a peak tricuspid regurgitation (TR) jet velocity of 2.7 m/s or greater, and who were free of known pulmonary vascular disease. Subjects were randomized in a 1:2:2 ratio to receive a single dose of either placebo, niacin 100 mg or niacin 500 mg, respectively. TR jet velocities were measured immediately before, and 1 hour post dose, corresponding to peak niacin absorption and prostaglandin release. The primary endpoint was the change in mean TR jet velocity measured over ten successive cardiac cycles. Results The baseline mean estimated right ventricular systolic pressure (RVSP) for all 49 subjects (25 male) was 51.9 ± 12.1 mm Hg. The primary endpoint of mean change in TR jet velocity was 0.016 ± 0.065 m/s in the placebo group, compared to −0.017 ± 0.065 m/s with niacin 100 mg, and −0.063 ± 0.038 m/s with niacin 500 mg (P = 0.63). The change in maximum estimated RVSP across the three drug groups was 0.2 ± 1.6 mm Hg, −1.3 ± 1.8 mm Hg and −2.2 ± 1.2 mm Hg (P = 0.62). In exploratory pairwise analysis in the high-dose niacin group (500 mg), the reduction in mean RVSP was from 50.9 ± 9.4 mm Hg to 48.7 ± 10.0 mm Hg (P = 0.09). Conclusions A single dose of immediate-release niacin (100 mg or 500 mg) had no significant effect on RVSP 1 hour post administration. A nonsignificant dose-dependent trend for a modest reduction in RVSP, most notable in the 500 mg group, was noted. (ISRCTN number 12353191, registered April 23, 2015).